Primary squamous cell carcinoma of the ovary. Review of the literature - Luo, Yan; Bian, Ce (Frontiers in Oncology, 2022)
Pure primary ovarian squamous cell carcinoma (oSCC) is very rare, with about 42 cases have been reported in the literature. Lacking effective treatment guidelines, the prognosis of oSCC is extremely poor. Here, we report a 52-year-old postmenopausal woman diagnosed with pure primary oSCC in our center. The patient received debulking surgery followed by chemotherapy with carboplatin, paclitaxel, and bevacizumab. The patient survived 11 months after surgery and died of tumor progression and multiple organ failure. We also present a review of the literature.